Digital Fatigue: Assessing Burnout In The Virtual Offices Era (Sandwich Generation Viewpoint) - Tito Wira Eka Suryawijaya; Muhammad Tata Rizky Setyo Utomo; Kusni Ingsih (Jurnal Telekomunikasi dan Informatika, 2023)
The perspective of the majority of individuals reflects the view that working from home is actually more tiring compared to the experience of working face-to-face. WFH workers are often faced with difficulties in managing and optimizing the use of their time, even though they are physically at home. This research aims to conduct an in-depth evaluation of the impacts that influence digital fatigue experienced by workers in the virtual office era, especially those with Sandwich Generation status. Quantitative methods with the SEM-PLS approach were used with a census sample of 582 respondents. The findings indicate that the digital fatigue experienced by the Sandwich Generation is not influenced by work pressure. This research makes a contribution by placing a focus on sandwich generation workers. This creates novelty because it brings a specific dimension of the sandwich generation into the virtual office context.